Introduction to the right of indigenous peoples - Ballón Aguirre, Francisco (2002)
This is an "introduction" to the law of indigenous peoples. Under that word I understand the necessary preparation to reach the proposed goal, in this case, to define what is understood as the right of indigenous peoples and the complications involved in that task. No book has been written on this subject in Peru. Indigenous rights are generally presented as an implicit issue in the approach adopted, for example, referring to peasant or native communities or to some international agreement. The legal idea of ​​the right of peoples, despite its antiquity, continues to motivate heated discussions, especially when it refers to indigenous peoples and self-determination.